Minimally invasive ileal ureter replacement: Comparative analysis of robot‐assisted laparoscopic versus conventional laparoscopic surgery. Issue 3 (24th February 2021) - Zhu, Weijie; Xiong, Shengwei; Fang, Dong; Hao, Han; Zhang, Lei; Xiong, Gengyan; Yang, Kunlin; Zhang, Peng; Zhu, Hongjian; Cai, Lin; Li, Xuesong; Zhou, Liqun
Abstract: Background: This study is an initial comparative analysis of perioperative and intermediate‐term functional outcomes between patients who underwent robot‐assisted laparoscopic (RALS) or conventional laparoscopic surgery (LS). Materials and Methods: A total of 25 patients who underwent ileal ureter replacement (10 RALS and 15 LS) were followed by functional cine magnetic resonance urography (MRU) combined with a modified Whitaker test. Also, the characteristics, perioperative data and functional outcomes of the patients were compared. Results: The estimated blood loss, postoperative hospital stay and time to oral intake were significantly lower in the RALS group. At the median 14‐month follow‐up, all the patients showed improved renal function and were symptom‐free, with no signs of leakage or stenosis observed by cine MRU combined with a modified Whitaker test. Conclusions: RALS with an extracorporeal bowel resection is feasible and appears to be safe, with quick postoperative recovery and encouraging outcomes.